Scraping force characteristics of frost formed on vertical cooling surfaces having different structures and wettability. (May 2019) - Li, Yingling; Li, Minxia; Utaka, Yoshio; Daitoku, Tadafumi.; Ohkubo, Hidetoshi; Yang, Chengjuan
Abstract: Frost formation and deposition on cooling surface inevitably cause serious damage as well as economic losses. To establish effective technologies for removing frost mechanically, the scraping force required to remove frost on vertical cooling surfaces was studied experimentally. The four types of copper surfaces investigated were a flat surface, micro-machined surface, laser fabricated surface, and hydrophobic surface. The results revealed that the scraping force increased with frost formation. With a distance less than 0.2 mm, the scraping force seems to increase exponentially. The surface structure and wettability considerably affect the freezing process and the growth of the initial frost crystals. The growth of frost could be delayed by 30% by micro-machining the cooling surface, which made the frost layer looser and easier to scrape off. The scraping force of the laser fabricated surface was approximately four times that of the hydrophobic surface at a height of 0.01 mm.